Comment on Baltic provenance of top-Famennian siliciclastic material of the northern Rhenish Massif, Rhenohercynian zone of the Variscan orogen, by Koltonik et al., International Journal of Earth Sciences (2018) 107:2645–2669 - Pereira, M. Francisco (2019)
Koltonik et al. (Int J Earth Sci 107:2645–2669, 2018) evidence that the Late Devonian siliciclastic rocks from the Rheno- Hercynian Zone, in Germany, derived from Baltica and Scandinavian Caledonides. This finding together with what is known about the provenance of the Pulo do Lobo and South Portuguese zones, in Portugal and Spain, reinforces the probability that Late Devonian basins may have been sourced from distinct terranes placed along the Variscan suture. Our comment intends to underline changes in the provenance of the Late Devonian basins along the active margin of Laurussia, and also, to improve the correlation model for the Variscan tectonic units from SW Iberia and Germany.